PENGAKUAN DAN PELAKSANAAN PUTUSAN PENGADILAN ASING DI INDONESIA DALAM PERSPEKTIF HUKUM PERDATA INTERNASIONAL - Chorun Nissa; Miftahul Azhari; M. Zaki Mubaok; M. Rafli Tri Arta; M. Sadi Is (Journal of Innovative and Creativity (Joecy), 2026)
The increasing number of cross-border legal relationships has resulted in a growing number of civil disputes being resolved before foreign courts. This situation raises legal issues concerning the recognition and enforcement of foreign court judgments in Indonesia, particularly because there is no specific legal framework governing their recognition and execution. This study aims to analyze the legal framework for the recognition and enforcement of foreign court judgments in Indonesia from the perspective of Private International Law and to identify the practical challenges encountered in their implementation. The research employs a normative legal research method using statutory, conceptual, and comparative approaches. Legal materials were collected through library research, including primary, secondary, and tertiary legal sources, and analyzed qualitatively. The findings indicate that the Indonesian legal system generally does not allow the direct enforcement of foreign court judgments. Such judgments are commonly treated only as supporting evidence or as the basis for filing a new claim before an Indonesian court, except in specific circumstances provided for by international agreements or applicable legislation. Differences in legal systems, the principle of state sovereignty, and the absence of comprehensive regulations remain the primary obstacles to the effective recognition and enforcement of foreign judgments. Therefore, regulatory reform and stronger international cooperation are necessary to enhance legal certainty, justice, and legal protection in cross-border civil legal relations.